THE DETERMINANTS OF DOMESTIC TOURISM: CASE IN iNDONESIA - Prasetyo, Ahmad Danu; Qurrota A’yun, Safira Asti (Journal of Business and Management, 2018)
Abstract. Development of tourism in Indonesia can be seen from the number of tourist arrivals in Indonesia both domestic and international that continuously increase. It affects to the increasing in contribution tourism sector into Indonesian economy. Most of tourism activity in Indonesia is generated by domestic tourist which weight 96.60% during 2009-2016. Domestic tourism can contribute in consumption, value added, and employment to Indonesian economy. In 2019, Indonesian Minister of Tourism has target to increase contribution of tourism in GDP to 8%. The precise strategy is needed to achieve the target. With knowing the factor that can influence the number of domestic tourist to do domestic tourism activities, it can easier to make strategy to achieve the target. This research is conducted to investigate the impact of factors on domestic tourism in Indonesia. There are three factors of number of domestic tourist arrivals in Indonesia that will be used in this research; tourists’ income, price of goods and services, and number of accommodation. Panel data regression was used. Based on Hausman Test, fixed-effect panel regression is the appropriate model that describe the problem in this research. All independent variables were significantly affect number of domestic tourist arrivals with positive relationship. Fixed-effect panel regression indicate that 64.64% of the variation in Indonesian domestic tourist inflows could be explained all independent variables. Tourists’ income, price of goods and services, and accommodation are determinants of domestic tourist in making travel decision. Keywords: determinants, domestic tourism, Hausman test, Indonesia, panel data